The Impact of Early Levothyroxine Replacement in Subclinical Hypothyroidism on Glycemic Control Parameters and Quality of Life in Adult Patients - Mowafy, Maha; Rushdy, Eman Ahmed; Rakha, Maha; Elshekheiby, Eman; Soliman, Saeed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Subclinical hypothyroidism is diagnosed by increased level of serum thyroid-stimulating hormone (TSH) with normal levels of free triiodothyronine (FT3) and free thyroxine (FT4). Controversy exists concerning the early treatment of subclinical hypothyroidism with levothyroxine when TSH level is below 10 mIU/L. AIM: This stud aims to quantify the effects of a 3-month trial of levothyroxine replacement on quality of life in SCH patients with TSH level less than 10 mIU/L as primary outcome and fasting blood sugar and HbA1C levels as secondary outcome. METHODS: This was a randomized controlled trial. It was carried out on subjects between 18 and 65 years, of both sexes attending the family medicine outpatient clinic at Cairo University Hospitals with untreated symptomatic mild subclinical hypothyroidism. Simple randomization was performed by assigning random numbers from random number table. Quality of life (Short-Form 36 Questionnaire) as well as fasting blood sugar levels and HbA1C were assessed before the replacement of levothyroxine and 3 months after starting treatment in the subclinical hypothyroidism patients (intervention group) and were compared to the control group. RESULTS: The median of role limitations due to emotional problems, social functioning, and health change was higher in the intervention group in comparison with the control group. Moreover, the median scores of all general health questionnaire items showed significant positive statistical changes in the intervention group. There was also a significant improvement in glycemic control reflected in lower HbA1C levels and FBS. CONCLUSION: The results of our study highlight the positive effect of early substitution with levothyroxine in subclinical hypothyroid patients regarding the quality of life and glycemic control in Egypt and support the argument for replacement.